Microshear Bond Strength of Composite to Dentin Using Self-etch and Etch and Rinse Adhesives – A Systematic Review and Meta-analysis - Tanvi Sanjay Satpute; Sanjyot Mulay; Divya Naik (Journal of International Clinical Dental Research Organization, 2025)
Objectives: A systematic review was conducted to determine whether bonding with self-etch (SE) adhesive system is more effective as compared to etch-and-rinse (ER) adhesive system. Background: Dental adhesives are integral in achieving durable bonds between resin composite and tooth structures. SE and ER systems differ in their application, with varying advantages and challenges. Materials and Methods: The following databases were searched for review: PubMed/MEDLINE, EBSCOhost, and Google Scholar. Based on the defined inclusion and exclusion criteria, the studies included measured microshear bond strength (µSBS) of SE and ER type of dental adhesives on human dental tissues of sound tooth structure origin at various periods. Water storage was used as the aging technique in the studies that were chosen. Statistical analysis was performed for outcome measurements compared at 24 h, 3 months, and 6 months of water storage using Review Manager 5.3. Results: From the search conducted, 13 articles were included in the systematic review, of which all 13 were included for meta-analysis. After 24 h (P = 0.02) and 3 months (P = 0.001) of water storage, a significant difference was seen between the two groups’ mean µSBS, favoring the SE group. Although at 6 months (P = 0.46), the comparison was statistically not significant. Conclusion: The meta-analysis showed µSBS is higher with the SE groups compared to ER bonding systems.